A Single L/D-Substitution at Q4 of the mInsA2-10 Epitope Prevents Type 1 Diabetes in Humanized NOD Mice - Zhang, Mengjun; Wang, Yuanqiang; Li, Xiangqian; Meng, Gang; Chen, Xiaoling; Wang, Lina; Lin, Zhihua; Wang, Li (Frontiers in Immunology, 2021)
Autoreactive CD8+ T cells play an indispensable key role in the destruction of pancreatic islet β-cells and the initiation of type 1 diabetes (T1D). Insulin is an essential β-cell autoantigen in T1D. An HLA-A*0201-restricted epitopes of insulin A chain (mInsA2-10) is an immunodominant ligand for autoreactive CD8+ T cells in NOD.β2mnull.HHD mice. Altered peptide ligands (APLs) carrying amino acid substitutions at T cell receptor (TCR) contact positions within an epitope are potential to modulate autoimmune responses via triggering altered TCR signaling. Here, we used a molecular simulation strategy to guide the generation of APL candidates by substitution of L-amino acids with D-amino acids at potential TCR contact residues (position 4 and 6) of mInsA2-10, named mInsA2-10DQ4 and mInsA2-10DC6 respectively. We found that administration of mInsA2-10DQ4, but not DC6, significantly suppressed the development of T1D in NOD.β2mnull.HHD mice. Mechanistically, treatment with mInsA2-10DQ4 not only notably eliminated mInsA2-10 autoreactive CD8+ T cell responses, but also prevented the infiltration of CD4+ T and CD8+ T cells, as well as the inflammatory responses in the pancreas of NOD.β2mnull.HHD mice. This study provides a new strategy for the development of APL vaccines for T1D prevention.